Strategic Management of Educational Institutions: A Balanced Scorecard Perspective - Gilman Mawardi; Hasbiyallah Hasbiyallah; Nurul Khoirunnisa; Fauziah Habibilah (Al-Qalam Institute, 2025)
This study examines the strategy for developing educational institutions through the integration of the Balanced Scorecard (BSC) at Madrasah Tsanawiyah Negeri. The research aims to analyze the implementation of BSC as a strategic management tool, identify supporting and inhibiting factors, and evaluate its impact on academic and non-academic performance. The research method employs a qualitative case study approach, involving in-depth interviews and document analysis. The results indicate that Madrasah Tsanawiyah Negeri has adopted BSC principles in its Strategic Plan 2020–2024, although the term BSC is not explicitly used. The implementation of BSC has contributed to improved budget transparency, stakeholder participation, and teacher competence. However, challenges such as cultural resistance, limited ICT infrastructure, and administrative burdens remain obstacles. The study also reveals that the integration of Islamic values such as shura (consultation) and amanah (trustworthiness) strengthens BSC implementation. Recommendations include simplifying performance indicators, human resource training, and technology optimization. This study provides theoretical contributions to the adaptation of BSC in Islamic education contexts and practical guidance for other madrasah.